PUSAT KEBUGARAN WANITA DI TANAH GROGOT DENGAN PENDEKATAN METAFORA - Fitriani, Rahmatul Jum’ah; Andini, Dila Nadya (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Fitness centers have the impression of being too manly because the majority of users are men, which makes women dominated, resulting in discomfort when doing fitness activities in public places where people of the opposite sex are mixed up. There is a need for a fitness center specifically for women that can accommodate women's fitness activities and have a woman's identity and image. To realize this, the design concept applied is to use a metaphorical approach that adopts women as the metaphorical object. The embodiment of the metaphor used is to adopt the shape of a flower basket, which is a place that can be used to collect and care for various types of flowers. This is in line with the realization of 'Woman healthy space' where women are often metaphorized as 'flowers' and then the flower basket becomes a 'container', a fitness center which becomes a gathering place for women to do fitness activities to be healthy.